Identifikasi Kemampuan Berpikir Kritis Siswa dengan Menggunakan Five-Tier Multiple Choice pada Materi Hidrolisis Garam - Pratiwi Hassan; Lukman Abdul Rauf Laliyo; Deasy Natalia Botutihe; Romario Abdullah (Universitas Pendidikan Mandalika Mataram, 2020)
This study aims to determine the critical thinking skills of high school students on salt hydrolysis. This research is quantitative descriptive. The population used in this study were all class XI IPA SMA in Gorontalo with a total sample of 64 respondents. Collecting data using a five-level multiple choice test instrument on salt hydrolysis material with an instrument validity value of 100%. The data analysis technique used in this research is descriptive quantitative. The results obtained the percentage of indicators of critical thinking skills, namely the focus criteria or Q1 level an average of 77.60%, the Reason criteria or Q2 level of 23.95%, the inference criteria or Q3 level of 8.85%, at Situation criteria or the Q4 level of 4.34% and the Clarity criteria or the Q5 level of 3.12%. Based on the results of the study it can be concluded that the ability of high school students to think critically on salt hydrolysis is 51.56% of students are in the very low category, 46.87% of students are in the low category and 1.56% of students are in the moderate category.